Oxford school spelling, punctuation and grammar dictionary (Oxford : Oxford University Press, 2013)
"With a clear, colour layout to make it easy to navigate, the book is in two parts. The first part is a reference section of simple rules, tips, and examples to help students spell, punctuate, and write correctly in school, in exams, and at home. This divides into three sections - Spelling, Punctuation, and Grammar. The second part is an alphabetical word list of common tricky words, with inflections, but no meanings. This list highlights, using analysis from the Oxford Children's Corpus, words that are most frequently misspelt by this age group, to target and rectify these common mistakes. There are helpful tips to guide the user around the alphabetical list to the word they are looking for, and helpful notes at key words to aid correct spellings. It will be a valuable resource for preparation for students taking exams with increased focus on accurate spelling and grammar. It will be a user-friendly resource for pupils to correct their own spellings and improve their spelling techniques and grammar. The accessible format will also provide an invaluable quick guide for spelling, punctuation marks, and grammar rules for teachers and parents as well" -- Publisher description
Includes index
Primary
Keywords: English language -- Grammar -- Dictionaries; English language -- Orthography and spelling -- Dictionaries